THE USE OF VIDEO LEARNING LOCAL WISDOM CONTENT BASED ON THE YOUTUBE PLATFORM AS GEOGRAPHY LEARNING RESOURCES - Rohman, Slamet Nopharipaldi; Widyanti, Triani (International Conference On Social Science Education, 2024)
This research aims to develop and analyze the effectiveness of learning videos that integrate local wisdom content, based on the YouTube platform as a geographic learning resource. In the current digital era, YouTube has become one of the most popular learning media among students, making it easy to access and interesting to watch. Indonesia's rich culture and local wisdom, as well as the integration of local content in geography learning, can enrich students' understanding of the local environment and culture. This research method uses a research and development (R&D) approach which begins with the process of making videos, validation tests by material and media experts, as well as trials on students as research subjects. The research results show that the learning videos developed not only increase students' interest in learning but also deepen their understanding of local wisdom-based geography material. Students responded positively to the use of this video, showing that integrating local wisdom in learning material can increase the relevance of the material to students' daily lives. YouTube-based learning videos have also proven to be an effective medium for delivering material interestingly and interactively. Thus, local wisdom-based learning videos on YouTube have great potential as an innovative and relevant learning resource in the context of geography learning in the current digital era.